Long-Term Outcomes After Severe Shock. Issue 2 (February 2015) - Pratt, Cristina M.; Hirshberg, Eliotte L.; Jones, Jason P.; Kuttler, Kathryn G.; Lanspa, Michael J.; Wilson, Emily L.; Hopkins, Ramona O.; Brown, Samuel M.
Abstract : ABSTRACT: Severe shock is a life-threatening condition with very high short-term mortality. Whether the long-term outcomes among survivors of severe shock are similar to long-term outcomes of other critical illness survivors is unknown. We therefore sought to assess long-term survival and functional outcomes among 90-day survivors of severe shock and determine whether clinical predictors were associated with outcomes. Seventy-six patients who were alive 90 days after severe shock (received ≥1 μg/kg per minute of norepinephrine equivalent) were eligible for the study. We measured 3-year survival and long-term functional outcomes using the Medical Outcomes Study 36-Item Short-Form Health Survey, the EuroQOL 5-D-3L, the Hospital Anxiety and Depression Scale, the Impact of Event Scale-Revised, and an employment instrument. We also assessed the relationship between in-hospital predictors and long-term outcomes. The mean long-term survival was 5.1 years; 82% (62 of 76) of patients survived, of whom 49 were eligible for follow-up. Patients who died were older than patients who survived. Thirty-six patients completed a telephone interview a mean of 5 years after hospital admission. The patients' Physical Functioning scores were below US population norms ( P < 0.001), whereas mental health scores were similar to population norms. Nineteen percent of the patients had symptoms of depression, 39% had symptoms of anxiety, and 8% had symptoms of posttraumatic stress disorder. Thirty-six percent were disabled, and 17% were working full-time. Early survivors of severe shock had a high 3-year survival rate. Patients' long-term physical and psychological outcomes were similar to those reported for cohorts of less severely ill intensive care unit survivors. Anxiety and depression were relatively common, but only a few patients had symptoms of posttraumatic stress disorder. This study supports the observation that acute illness severity does not determine long-term outcomes. Even extremely critically ill patients have similar outcomes to general intensive care unit survivor populations.